Association between cheese consumption but not other dairy products and lower obesity risk in adults. - Gladys Morales; Claudia Bugueño; Rodrigo Valenzuela; Rodrigo Chamorro; Carla Leiva; Martin Gotteland; Silvana Trunce-Morales; Nicolás Pizarro-Aranguiz; Samuel Durán-Agüero (PLoS ONE)
Introduction Some studies have associated dairy consumption with a lower risk of obesity. However, these studies are concentrated in developed countries with high dairy consumption. In developing countries, the evidence is scarce. This study aimed to evaluate the association between the consumption of different types of dairy products and obesity in Chilean adults. Materials and methods A cross-sectional study, stratified by sex and age, was carried out using a validated online survey to assess the consumption of dairy products among adults living in Chile. Dairy product consumption was then classified into tertiles. Obesity was determined based on self-reported body mass index (BMI) ≥ 30 kg/m2. Logistic regression models were used to assess the association between dairy consumption and obesity, adjusting for several confounding variables. Results In total, 2008 participants were included in the analyses. Forty-seven percent, 39% and 14% belonged to the <35 years, 35-60 years, and ≥60-year groups, respectively. 55% were female, 86% had a low-medium socioeconomic level. Cow-derived cheese, milk, and yogurt were the most commonly consumed dairy products. Obese participants had a lower total consumption of dairy products (17.1%) than normal-weight subjects (25.7%, p<0.05). Higher cheese intake was significantly associated with a lower obesity risk (ORadj: 0.70; 95%CI 0.51-0.96, p<0.05). Other types of dairy products and total consumption of dairy products were not significantly associated. Discussion and conclusions Habitual cheese consumption, but not other dairy products, was associated with a lower risk of obesity in this sample of Chilean adults.